Race migrations : Latinos and the cultural transformation of race - Roth, Wendy D. (Stanford University Press, 2012)
In this groundbreaking study of Puerto Rican and Dominican migration to the United States, Wendy D. Roth explores the influence of migration on changing cultural conceptions of race--for the newcomers, for their host society, and for those who remain in the countries left behind. Just as migrants can gain new language proficiencies, they can pick up new understandings of race. But adopting an American idea about race does not mean abandoning earlier ideas. New racial schemas transfer across borders and cultures spread between sending and host countries. Behind many current debates on immigration.